Preconditioning of Adipose-Derived Mesenchymal Stem-Like Cells with Eugenol Potentiates Their Migration and Proliferation In Vitro and Therapeutic Abilities in Rat Hepatic Fibrosis - Moustafa Fathy; Motonori Okabe; Eman M. Othman; Heba M. Saad Eldien; Toshiko Yoshida (Molecules, 2020)
Mesenchymal stem cells (MSCs) have considerable therapeutic abilities in various disorders, including hepatic fibrosis. They may be affected with different culture conditions. This study investigated, on molecular basics, the effect of pretreatment with eugenol on the characteristics of adipose tissue-derived MSCs (ASCs) in vitro and the implication of eugenol preconditioning on the in vivo therapeutic abilities of ASCs against CCl4-induced hepatic fibrosis in rats. The effect of eugenol on ASCs was assessed using viability, scratch migration and sphere formation assays. Expressions of genes and proteins were estimated by immunofluorescence or qRT-PCR. For the in vivo investigations, rats were divided into four groups: the normal control group, fibrotic (CCl4) group, CCl4+ASCs group and CCl4 + eugenol-preconditioned ASCs (CCl4+E-ASCs) group. Eugenol affected the viability of ASCs in a concentration- and time-dependent manner. Eugenol improved their self-renewal, proliferation and migration abilities and significantly increased their expression of c-Met, reduced expression 1 (Rex1), octamer-binding transcription factor 4 (Oct4) and nanog genes. Furthermore, E-ASCs showed more of a homing ability than ASCs and improved the serum levels of ALT, AST, albumin, total bilirubin and hyaluronic acid more efficient than ASCs in treating CCl4-induced hepatic fibrosis, which was confirmed with histopathology. More interestingly, compared to the CCl4+ASCs group, CCl4+E-ASCs group showed a lower expression of inducible nitric oxide synthase (iNOS), monocyte chemoattractant protein-1 (MCP-1), cluster of differentiation 163 (CD163) and tumor necrosis factor-α (TNF-α) genes and higher expression of matrix metalloproteinase (MMP)-9 and MMP-13 genes. This study, for the first time, revealed that eugenol significantly improved the self-renewal, migration and proliferation characteristics of ASCs, in vitro. In addition, we demonstrated that eugenol-preconditioning significantly enhanced the therapeutic abilities of the injected ASCs against CCl4-induced hepatic fibrosis.